A corticostriatal projection for sound-evoked and anticipatory motor behavior following temporal expectation. Issue 1 (14th November 2022) - Huang, Wushuang; Wang, Yuting; Qin, Jing; He, Chao; Li, Yurong; Wang, Yan; Li, Min; Lyu, Jing; Zhou, Zhenqiao; Jia, Hongbo; Pakan, Janelle; Xie, Peng; et al.
Abstract : The ability to form predictions based on recent sensory experience is essential for behavioral adaptation to our ever-changing environment. Predictive encoding represented by neuronal activity has been observed in sensory cortex, but how this neuronal activity is transformed into anticipatory motor behavior remains unclear. Fiber photometry to investigate a corticostriatal projection from the auditory cortex to the posterior striatum during an auditory paradigm in mice, and pharmacological experiments in a task that induces a temporal expectation of upcoming sensory stimuli. We find that the auditory corticostriatal projection relays both sound-evoked stimulus information as well as predictive signals in relation to stimulus timing following rhythmic auditory stimulation. Pharmacological experiments suggest that this projection is required for the initiation of both sound-evoked and anticipatory licking behavior in an auditory associative-learning behavioral task, but not for the general recognition of presented auditory stimuli. This auditory corticostriatal projection carries predictive signals, and the posterior striatum is critical to the anticipatory stimulus-driven motor behavior.